Wastewater crisis in East African cities: challenges and emerging opportunities - Meserecordias Wilfred Lema (Discover Environment)
Abstract This review paper aims to examine the key challenges associated with wastewater management in major cities of the East African region and explore the emerging opportunities for addressing this crisis. An extensive database search identified 100 peer-reviewed publications related to wastewater crisis in East Africa. The reviewed literature was analysed and synthesized to develop an understanding of the topic. The findings from this review have shown that less than 55% of the East African population (30% in Tanzania, 40% in Uganda, 50% in Kenya, 40% in Rwanda, 20% in Burundi, 30% in Ethiopia, 50% in Sudan, and 15% in Somalia) is connected to sewers systems. Additionally, the study has revealed the following issues as the main challenges facing wastewater management in East Africa; poor infrastructure, regulatory and institutional deficiencies, poor financing and cost recovery mechanism, and poor community participation and utility management, which in turn results to potential environmental and public health implications. This paper has also identified possible innovative strategies and emerging opportunities for sustainable wastewater management. These include; decentralized wastewater treatment systems, resource recovery and reuse, public–private partnerships, policy and governance reforms and the use of modern technologies such as membrane filtration, advanced oxidation processes, and electrochemical treatment methods. In addition, the role of policy and governance reforms in enabling sustainable wastewater management in East Africa has also been emphasized, in this paper. The findings of this review emphasize the urgent need for comprehensive policies, investments, and collaborative efforts to address the wastewater crisis and harness the potential benefits of wastewater as a resource.